LITTIP/Lgr6/HnRNPK complex regulates cementogenesis via Wnt signaling - Tiancheng Li; Han Wang; Yukun Jiang; Shuo Chen; Danyuan Huang; Zuping Wu; Xing Yin; Chenchen Zhou; Yuyu Li; Shujuan Zou (Nature Publishing Group, 2023)
Abstract Orthodontically induced tooth root resorption (OIRR) is a serious complication during orthodontic treatment. Stimulating cementum repair is the fundamental approach for the treatment of OIRR. Parathyroid hormone (PTH) might be a potential therapeutic agent for OIRR, but its effects still lack direct evidence, and the underlying mechanisms remain unclear. This study aims to explore the potential involvement of long noncoding RNAs (lncRNAs) in mediating the anabolic effects of intermittent PTH and contributing to cementum repair, as identifying lncRNA-disease associations can provide valuable insights for disease diagnosis and treatment. Here, we showed that intermittent PTH regulates cell proliferation and mineralization in immortalized murine cementoblast OCCM-30 via the regulation of the Wnt pathway. In vivo, daily administration of PTH is sufficient to accelerate root regeneration by locally inhibiting Wnt/β-catenin signaling. Through RNA microarray analysis, lncRNA LITTIP (LGR6 intergenic transcript under intermittent PTH) is identified as a key regulator of cementogenesis under intermittent PTH. Chromatin isolation by RNA purification (ChIRP) and RNA immunoprecipitation (RIP) assays revealed that LITTIP binds to mRNA of leucine-rich repeat-containing G-protein coupled receptor 6 (LGR6) and heterogeneous nuclear ribonucleoprotein K (HnRNPK) protein. Further co-transfection experiments confirmed that LITTIP plays a structural role in the formation of the LITTIP/Lgr6/HnRNPK complex. Moreover, LITTIP is able to promote the expression of LGR6 via the RNA-binding protein HnRNPK. Collectively, our results indicate that the intermittent PTH administration accelerates root regeneration via inhibiting Wnt pathway. The lncRNA LITTIP is identified to negatively regulate cementogenesis, which activates Wnt/β-catenin signaling via high expression of LGR6 promoted by HnRNPK.